Identidades Flashcards
Cos^2 (x) + sin^2 (x) =
1
Sec^2 (x) - tan^2 (x) =
1
Csc^2 (x) - cot^2 (x) =
1
1
Cos^2 (x) + sin^2 (x) = 1
Sec^2 (x) - tan^2 (x) = 1
Csc^2 (x) - cot^2 (x) = 1
Sin (x) =
+/- Raiz (1-cos^2 (x) )
1/ csc (x)
+/- Raiz (1-cos^2 (x) ) =
Sin (x)
Cos ( x) =
+/- raiz ( 1- sin^2 (x))
1/ sec x
+/- raiz ( 1- sin^2 (x))=
Cos (x)
Sin (x +/- y ) =
Sin x cos y +/- cos x sin y
Sin x cos y +/- cos x sin y=
Sin (x +/- y )
Cos ( x +/- y ) =
Cos (x) cos (y) -/+ sin (x) sin (y)
Cos (x) cos (y) -/+ sin (x) sin (y)=
Cos ( x +/- y )
Tan ( x +/- y ) =
= (tan (x) +/- tan (y) ) / ( 1 -/+ tan (x) tan (y)
(tan (x) +/- tan (y) ) / ( 1 -/+ tan (x) tan (y) =
Tan ( x +/- y )
Csc ( x +/- y ) =
1/ (sin (x +/- y )
1/ (sin (x +/- y ) =
Csc ( x +/- y )
Sec (x +/- y ) =
= 1/ ( cos ( x +/- y )
1/ ( cos ( x +/- y ) =
Sec (x +/- y )
Cot ( x +/- y ) =
= (cot x cot y - /+ 1 ) / ( cot y + /- cot x )
(cot x cot y - /+ 1 ) / ( cot y + /- cot x ) =
Cot ( x +/- y )
Sin 2x
Sin 2x
= 2 sin x cos x
= 2 sin x cos x
Sin 2x
Cos 2x
Cos 2x = 1- tan^2 x / 1 + tan^2 x = cos^2 x - sin^2 x = 2 cos^2 x - 1 = 1 - 2 sin^2 x
= 1- tan^2 x / 1 + tan^2 x
= cos^2 x - sin^2 x
= 2 cos^2 x - 1
= 1 - 2 sin^2 x
Cos 2x
Tan 2x
Tan 2x
= 2 tan x / 1- tan^2 x
2 tan x / 1- tan^2 x =
Tan 2x
Cot 2x
Cot 2x
=( cot^2 x - 1 ) / 2 cot x
( cot^2 x - 1 ) / 2 cot x=
Cot 2x
Sin x/ 2 =
Sin x/ 2 = +/- raiz ( 1- cos x / 2 )
+/- raiz ( 1- cos x / 2 ) =
Sin x/ 2
+/- raiz ( 1 + cos x / 2 ) =
Cos x/2 =
+/- raiz ( 1 + cos x / 2 )
+/- raiz ( 1 + cos x / 2 ) =
Cos x/2 =
Tan x/2
Tan x/2
= sin x / 1 + cos x
= 1- cos x / sin x
= 1- cos x / sin x
= sin x / 1 + cos x
Tan x/2
Sin x =
1 / csc x
Cos x =
1 / sec x
Tan x =
1 / cot x
Sen x / cos x
Cot x =
1 / tan x
Sec x =
1 / cos x
Csc x =
1 / sin x